2007
DOI: 10.2298/psi0704485s
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the lexical personality descriptors in Serbian language

Abstract: Two studies, both originating from a larger psycholexical study in Serbian language, are presented here. Two questionnaires, Lexi and PL have been constructed in the psycholexical study. The questionnaires differ by the formulation of their respective items: while the items of the Lexi contain adjectives, the items of the PL are in the form of statements. The first study presented in this paper examines the latent structure of the Lexi questionnaire, while the second one deals with the latent structure of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
0
12
0
3
Order By: Relevance
“…We compared the number of culled terms with other psycholexical studies. The number of terms culled has typically ranged from 326 in Hebrew (Almagor, Tellegen, & Waller, ) to 2,027 in Polish (Szarota, Ashton, & Lee, 2007), whereas terms retained for participant ratings have ranged from 264 in Serbian (Smederevac, Mitrovic, & Colovic, ) to 314 in Italian (Di Blas & Forzi, ) and to 413 in Chinese (Zhou et al, ). While some may view our culled list of 204 as smaller than other similar studies, we argue that this may be due to idiosyncrasies of the Arabic language and its corresponding dictionaries (Daouk‐Öyry et al, ), which led to the removal of redundant and unfamiliar words (retaining a much larger number of words would have implied that unfamiliar words would appear in the list).…”
Section: Resultsmentioning
confidence: 99%
“…We compared the number of culled terms with other psycholexical studies. The number of terms culled has typically ranged from 326 in Hebrew (Almagor, Tellegen, & Waller, ) to 2,027 in Polish (Szarota, Ashton, & Lee, 2007), whereas terms retained for participant ratings have ranged from 264 in Serbian (Smederevac, Mitrovic, & Colovic, ) to 314 in Italian (Di Blas & Forzi, ) and to 413 in Chinese (Zhou et al, ). While some may view our culled list of 204 as smaller than other similar studies, we argue that this may be due to idiosyncrasies of the Arabic language and its corresponding dictionaries (Daouk‐Öyry et al, ), which led to the removal of redundant and unfamiliar words (retaining a much larger number of words would have implied that unfamiliar words would appear in the list).…”
Section: Resultsmentioning
confidence: 99%
“…To our surprise, even though previous studies have systematically demonstrated the relationship between Extraversion and the usage of specific words in texts (Gill et al, 2009;Pennebaker & King, 1999), this personality dimension did not show a significant relationship with the choice of topics. This result might be the consequence of the cross-cultural differences in the content of this personality dimension (for example, see Čolović, Mitrović, & Smederevac, 2005;Smederevac et al, 2007) but further studies are needed in order to draw any valid conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Items are grouped in seven main scales corresponding to seven personality dimensions: Extraversion, Neuroticism, Conscientiousness, Aggressiveness 1 , Openness to experience, Positive valence and Negative valence (Smederevac et al, 2010). VP+2 questionnaire is derived from the LEXI questionnaire (Smederevac, Mitrović, & Čolović, 2007), which was based on the psycho-lexical study and the methodology of Tellegen and Waller and their Seven Factor Model of Personality Description (Waller, 1999). Compared to the five-factor model of personality (for example, see McCrae & John, 1992), the seven-factor model includes two additional evaluative categories named Positive valence and Negative valence (Waller, 1999).…”
Section: Samplementioning
confidence: 99%
“…Pored pet faktora koji se uobičajeno dobijaju u psiholeksičkim studijama, njihov HEXACO model sadrži i faktor Poštenje. Rezultati dosadašnjih kroskulturalnih istraživanja pokazuju opravdanost petofaktorske (Hendriks et al, 2003), ali i šestofaktorske (Ashton, Lee, de Vries, Perugini, Gnisci, & Sergi, 2006) i sedmofaktorske (Almagor, Tellegen, & Waller, 1995;Benet & Waller, 1995;Smederevac, Mitrović i Čolović, 2007) strukture leksičkih opisa ličnosti.…”
unclassified
“…Kako bi se proverila stabilnost ovakve strukture leksičkih deskriptora ličnosti, sprovedena je druga psiholeksička studija u sprskom jeziku (Smederevac, Mitrović i Čolović, 2007). Sa svake druge stranice Rečnika srpskog književnog jezika sa jezičkim savetnikom (Moskovljević, 2000) preuzet je prvi termin koji se odnosi na ličnost.…”
unclassified